Старуха Изергиль: рассказы / Максим Горький - Горький Максим (Школьная программа по чтению, 2019)
Экземпляры: ф.16 (20210621) / Инвентарный номер: 61028 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Г 71 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=411.2)6